2014
DOI: 10.1371/journal.pone.0091621
|View full text |Cite|
|
Sign up to set email alerts
|

Susceptibility to Chronic Mucus Hypersecretion, a Genome Wide Association Study

Abstract: BackgroundChronic mucus hypersecretion (CMH) is associated with an increased frequency of respiratory infections, excess lung function decline, and increased hospitalisation and mortality rates in the general population. It is associated with smoking, but it is unknown why only a minority of smokers develops CMH. A plausible explanation for this phenomenon is a predisposing genetic constitution. Therefore, we performed a genome wide association (GWA) study of CMH in Caucasian populations.MethodsGWA analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…After quality control, 717 heavy smokers with CMH (cases) and 1795 heavy smokers without CMH (controls) all with ≥20 pack-years were included for the analysis as previously published 16. Six SNPs were tested using multivariate logistic regression analysis under an additive model, with adjustment for ex-smokers or current smokers and the two population sites (Groningen and Utrecht).…”
Section: Methodsmentioning
confidence: 99%
“…After quality control, 717 heavy smokers with CMH (cases) and 1795 heavy smokers without CMH (controls) all with ≥20 pack-years were included for the analysis as previously published 16. Six SNPs were tested using multivariate logistic regression analysis under an additive model, with adjustment for ex-smokers or current smokers and the two population sites (Groningen and Utrecht).…”
Section: Methodsmentioning
confidence: 99%
“…Dijkstra and colleagues performed a GWAS meta-analysis in a total of 2,704 subjects with chronic bronchitis with or without airflow obstruction (which they termed chronic mucus hypersecretion) and 7,624 controls, finding an association with an intronic SNP in the SATB homeobox 1 (SATB1) transcription factor. [42] The SNP was shown to effect SATB1 expression levels in lung tissue. In addition, SATB1 expression was increased in airway biopsies of subjects with mucus hypersecretion.…”
Section: Gwas Of Additional Copd Phenotypesmentioning
confidence: 99%
“…Moreover, also some replication cohorts were underpowered and CMH is rather a rough estimate. However, we found suggestive evidence for a genetic contribution to CMH in the full population without stratification for COPD, thus suggesting that power would be more of a problem than the definition of CMH [14]. When we analyzed whether our previously reported gene SATB1 was associated with CMH in individuals with and without COPD, we also found that the significance was considerably reduced, p-values of rs6577641 being 2.52 10 −2 and 5.69 10 −2 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Information on CMH and smoking behavior was collected by questionnaires as published previously [14]. Spirometry was performed according to the European Respiratory Society guidelines, including forced expiratory volume in 1 sec (FEV 1 ) and forced vital capacity (FVC), without using a bronchodilator [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation